Salad for dinner : simple recipes for salads that make a meal - De Serio, Tasha (Taunton Press, 2012)
"This book features whole-meal salads that encompass everything from greens to meat and fish, dairy, and pasta and grain, that deliver healthful, year-round recipes that will satisfy vegetarians and meat-eaters alike"--